Numerical simulation of sulfur particle agglomeration at bends of high sulfur natural gas gathering pipelines based on Euler–PBM coupling - Huang, Jingyi; Liu, Gang; Fan, Shishui; Li, Bo; Li, Changjun (Scientific reports, 2024)
Sulfur deposition can result in an increase in the wall thickness of high-sulfur natural gas gathering pipelines, leading to issues like unstable pipeline flow. It is crucial to reveal the aggregation of sulfur particles at key locations of high-sulfur natural gas gathering pipelines to predict the location and amount of sulfur deposition in the pipelines. In this paper, the Euler–PBM (Population balance model) coupling is used to establish a numerical simulation model of gas–solid two-phase pipe flow accompanied by sulfur particle agglomeration in the pipe bends, focusing on the influence of sulfur particle volume fraction, pipe inclination angle and inlet flow velocity on sulfur particles agglomeration behavior. The results show that the sulfur particles have a significant agglomeration effect at the bend of the collecting pipeline, and the agglomeration growth occurs to different degrees throughout the bend, and the main area of sulfur particles agglomeration is near the top wall of the pipeline, followed by other areas near the wall of the pipeline. When the inlet volume fraction of sulfur particles was increased from 0.05 to 0.25%, and the inclination angle of the pipe was increased from 30° to 90°, the distribution range of sulfur particle size after agglomeration became wider, and the maximum size of sulfur particles was 187.56 μm, and the effect of sulfur particle agglomeration was enhanced; the inlet flow rate was increased from 3.0 to 9.0 m/s, and the reduction range of sulfur particle size after agglomeration was 5.68–9.87 μm. The maximum particle size of sulfur particles also decreased, and the effect of sulfur particle agglomeration was weakened.